Maternal and fetal outcome in antepartum haemorrhage: a study at tertiary care hospital - Kedar, Kshama; Uikey, Prashant; Pawar, Ashwini; Choudhary, Anuja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Antepartum hemorrhage (APH) complicates about 2-5% of pregnancies. Maternal and perinatal morbidity and mortality associated with APH can be reduced significantly by aggressive expectant management. The objective was to study the maternal and fetal outcome in APH and to assess the importance of early diagnosis and treatment Methods: This prospective study was conducted in the department of OBGY in IGGMC Nagpur from Dec 2013 to Nov.15. 131 cases of APH with gestational age >28 weeks were included. They were distributed according to type of APH into Abruptio Placentae (AP), Placenta Previa (PP) and Unclassified Haemorrhage (UH). Causes of APH were noted and maternal as well as perinatal outcome observed. Results: Out of 131, 51.91% was AP followed by PP (45.80%) and 2.29% of UH. Maximum patients belonged to 25 to 29 years age group (40.46%), which was statistically significant (p value 0.023). Maximum no. of patients who presented with APH was of more than 36 weeks of gestational age which was statistically significant (p value 0.0001). 52.94% had PIH as a causative factor of abruption while 41.67% had history of previous LSCS for PP. Anaemia was most common complication in APH followed by PPH. One patient died of renal failure in AP. Neonatal jaundice was the most common complication amongst the neonate followed by prematurity. Conclusions: Prevalence of APH was 2% with AP being most common cause followed by PP. Though maternal morbidity is reduced with modern management of APH, but timely diagnosis and intervention is necessary.